Fatigue in patients with hypothalamic syndrome – A cross-sectional analysis of the German childhood-onset craniopharyngioma cohort - Julia Beckhaus; Jale Özyurt; Aylin Mehren; Carsten Friedrich; Hermann L. Müller (EJC Paediatric Oncology)
Objective: Patients with suprasellar tumors are at risk for hypothalamic syndrome (HS), including fatigue and excessive daytime sleepiness. The aim of this cross-sectional study was to determine the severity of fatigue in patients with and without HS. Methods: Patients diagnosed with CP or pilocytic astrocytoma were recruited from the KRANIOPHARYNGEOM studies. Eligibility criteria were availability of one completed Multidimensional Fatigue Inventory-20 (MFI-20) questionnaire and complete medical records on criteria for HS. The associations between HS and levels of fatigue symptoms (MFI-20 sum score) were assessed. MFI-20 scores were compared to sex- and age-matched reference values from a German normative population. Results: Data on 41 patients, with a median age of 22 years, were available for analyses of which 25 (61 %) patients presented with HS. After adjustment for age and sex, patients with HS reported higher scores in the physical (β= 3.39 [95 %-CI:1.18–5.60]) and sum MFI-20 (β=11.42 [95 %-CI:2.06–20.79]) domain than patients without HS. Compared to reference values, all patients reported higher mean scores in each fatigue domain. Abnormal self-reported daytime sleepiness was reported in 6 of 25 (24 %) patients with HS. Regardless of the level of daytime sleepiness in patients with HS, the reported fatigue scores were high. Daytime sleepiness did not correlate with fatigue. Conclusions: Fatigue symptoms are present in patients with CP. However, patients with HS are more affected with physical and overall fatigue. It is crucial in clinical practice, to distinguish between daytime sleepiness and fatigue and to target patients with HS.